Marcion A New Perspective on his Life, Theology, and Impact - Moll, Sebastian 1980- (2010)
The main argument of the present article is that previous scholarship has turned Marcion's exegesis of Scripture upside down. He did not find the inspiration for his doctrine in the teachings of the Apostle Paul, it is the Old Testament and its portrait of an inconsistent, vengeful and cruel God which forms the centre of his theology. Marcion does not understand the Old Testament in the light of the New, he interprets the New Testament in the light of the Old.
Keywords: Apostles; Bible; Bible. Old Testament; Canon; Harnack; Heresy; Marcion; Old Testament; Paul, The Apostle, Saint; Theological Education